Forest Groundcover Restoration - Holly K. Ober; Jennifer L. Trusty (EDIS, 2009)
WEC269, a 5-page illustrated fact sheet by Holly K. Ober and Jennifer L. Trusty, provides an overview of seven steps to follow for a successful groundcover restoration project. Includes additional sources of information. Published by the UF Department of Wildlife Ecology and Conservation, November 2009.